Grazing Changed Plant Community Composition and Reduced Stochasticity of Soil Microbial Community Assembly of Alpine Grasslands on the Qinghai-Tibetan Plateau - Li, Yu; Dong, Shikui; Gao, Qingzhu; Fan, Chun; Fayiah, Moses; Ganjurjav, Hasbagan; Hu, Guozheng; Wang, Xuexia; Yan, Yulong; Gao, Xiaoxia; Li, Shuai (Frontiers in Plant Science, 2022)
Grazing is a substantial threat to the sustainability of grassland ecosystems, while it is uncertain about the variety of plant and soil microbial community and the linkages between them limit the comprehensive understanding of grazing ecology. We conducted an experiment on the effects of the grazing regimes rotational grazing (RG), continuous grazing (CG), and grazing exclusion (GE) on an alpine meadow in Qinghai-Tibetan Plateau. The differences of plant community composition, soil microbial community assembly mechanism, and taxonomic and functional composition between grazing regimes were examined, and the relationship between plant species and the soil microbes was assessed by constructing a co-occurrence network. The results showed that the plant community composition varied with the grazing regimes, while the soil microbial community composition did not vary with the grazing regimes. The soil bacterial functional composition was similar under RG and CG, while the soil fungal functional composition was similar under GE and RG. The soil microbial community under all grazing regimes was assembled mainly according to stochastic rather than deterministic mechanisms, and RG and CG reduced the relative importance of the stochastic ratio. At the microbial phylum level, CG and GE increased the relative abundance of Acidobacteria and Armatimonadetes and CG and RG increased the relative abundance of Elusimicrobia. In the network of plant species and soil microbial classes, plants and bacteria themselves were mainly positively linked (symbiosis and promotion), while plants and soil microbes were mainly negatively linked (competition). There were five microbial generalists in the network, which connected with many microbes, and four showed no difference in their abundance among the grazing regimes. Overall, the stable key microbes in the network and the fact that many of the plants are unconnected with microbes weakened the impact of grazing-induced changes in the plant community on soil microbes, probably resulting in the stable soil microbial community composition. Moreover, there was still a dominant and tolerant plant species, Kobresia pygmaea, that connected the plant and microbial communities, implying that the dominant plant species not only played a crucial role in the plant community but also acted as a bridge between the plants and soil microbes; thus, its tolerance and dominance might stabilize the soil microbial community.